PELATIHAN PERBANKAN TERKINI UNTUK GURU – GURU MGMP AKUNTANSI DAN PERBANKAN - Rokhmania, Nur Aini; Sistiyarini, Evi; Kristijadi, Emanuel (Universitas Mataram, 2024)
The Subject Teacher Discussion Group (MGMP) for Accounting and Banking in Surabaya City serves as a professional platform for Accounting and Banking teachers. In recent years, the banking industry has undergone rapid changes related to regulations and digitalization. The issue is that teachers' understanding of regulatory changes, digitalization developments, and fintech in banking is still low. This community service utilizes a Participatory Action Research (PAR) approach with four stages of activity: problem identification, planning, implementation, and training activity analysis. The training session featured three speakers covering topics on Banking Development, Lab Bank Applications, and Digital Accounting and Services. Analysis of the pre-test results showed an average score of correct answers at 51%, while the post-test reached 72%, indicating an improvement in teachers' understanding of regulatory changes, digitalization developments, and fintech in the banking sector.